Between Playing Hardball and Accommodating Generously? The Terms of Enlargement for the Integration of the German Democratic Republic Into the European Community - Alexander Klein (JCMS: Journal of Common Market Studies, 2025)
Do norms impact state action, or are they purely instrumental and subordinate to material interests? I approach this long-standing debate by analysing the European Union's (EU) enlargement terms. When the prospect of enlargement arises, the EU faces the dilemma of minimising resulting financial implications while fulfilling normative obligations to support new members. Historically, the EU responded both by discriminating new members from benefits or by exempting them from obligations. I claim that understanding the determinants of enlargement requires bridging theoretical divides in European Studies. I argue that states' material interests and norms are equally influential, resulting in enlargement terms being painstakingly negotiated compromises balancing both. The analysis focuses on the German Democratic Republic's (GDR) integration into the European Community (EC), where the EU's dilemma between material and normative principles was particularly pronounced. The mixed-methods analysis reveals nuanced enlargement terms with unprecedented exemptions, albeit of short duration.
Keywords: 330; differentiated integration; enlargement; European integration; European Union; German Democratic Republic